PENDIDIKAN KARAKTER BERBASIS APRESIASI DAN SANKSI: TELAAH KONSEPTUAL DALAM PERSPEKTIF AL-QUR’AN - Amran Amir; Muzakkir; Amri Amir (LP2M IAIN Sultan Amai Gorontalo, 2025)
ABSTRACT Character education is a fundamental pillar in shaping the personalities of young generations with noble morals, preparing them to face global challenges. This article explores character education based on appreciation and sanction from the perspective of the Qur’an through a conceptual study employing a library research approach. The method utilized is qualitative with thematic analysis techniques applied to Qur’anic verses, classical and modern tafsir, as well as relevant Islamic education literature. The findings reveal that the Qur’an provides appreciation for positive behavior through promises of reward and spiritual motivation, while also emphasizing the importance of sanctions as an educative moral control. The integration of appreciation and sanction is proven to foster the development of disciplined, responsible character aligned with universal values. The implication of this research underscores the necessity of implementing proportional and humanistic appreciation and sanction models in character education within schools or madrasahs. Keywords: Character education, Appreciation, Sanction